2019
DOI: 10.1080/10106049.2019.1595177
|View full text |Cite
|
Sign up to set email alerts
|

Geographical random forests: a spatial extension of the random forest algorithm to address spatial heterogeneity in remote sensing and population modelling

Abstract: Machine learning algorithms such as Random Forest (RF) are being increasingly applied on traditionally geographical topics such as population estimation. Even though RF is a well performing and generalizable algorithm, the vast majority of its implementations is still 'aspatial' and may not address spatial heterogenous processes. At the same time, remote sensing (RS) data which are commonly used to model population can be highly spatially heterogeneous. From this scope, we present a novel geographical implemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
139
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 237 publications
(191 citation statements)
references
References 30 publications
3
139
0
Order By: Relevance
“…However, predictor variables that describe the spatial location rather than the environmental properties are commonly included. Spatial coordinates are used especially often (Li et al, 2011;Langella et al, 2010;Shi et al, 2015;Janatian et al, 2017;Walsh et al, 2017;Jing et al, 2016;Wang et al, 2017;Georganos et al, 2019). Distances to certain points (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, predictor variables that describe the spatial location rather than the environmental properties are commonly included. Spatial coordinates are used especially often (Li et al, 2011;Langella et al, 2010;Shi et al, 2015;Janatian et al, 2017;Walsh et al, 2017;Jing et al, 2016;Wang et al, 2017;Georganos et al, 2019). Distances to certain points (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…As an evaluation metric to select the best model we selected the root mean squared error (RMSE) coming from the out-of-bag (OOB) predictions of the random forest (RF) regressor. RF is a decision-tree ensemble machine learning algorithm that has been shown resilient to overfitting and robust to model the complex non-linear relationships among satellite derived features and socio-economic and demographic indicators [16,30,33]. For optimizing the parameters of the three final RF models (P0, P1, P2) we used the cross-validation functions of the "caret" package in R statistical software [34,35].…”
Section: Model Selection and Spatial Optimization Methodsmentioning
confidence: 99%
“…The LULC products are publicly available with a LC map at 0.5 resolution and a LU map at the street block level ( Figure 4) [18,28]. These products have been successfully used for urban local climate zone validation [29] and population models at similar geographical scales [16,30]. The overall accuracy of the LC and LU maps was 89.5% and 79%, respectively [16].…”
Section: Very High-resolution (Vhr) Satellite Datamentioning
confidence: 99%
“…have tested random forest for different scenarios of spatial autocorrelation in the observations and confirmed that the presence of spatial autocorrelation leads to high variance of the residuals. ML algorithms accounting for autocorrelated observations have recently been formulated, such as geographical random forest(Georganos et al, 2019), or spatial ensemble techniques(Jiang et al, 2017). The two methods boil down to geographically weighted regression by fitting spatially local sub-models using only neighbouring observations Jiang et al (2017).…”
mentioning
confidence: 99%
“…The two methods boil down to geographically weighted regression by fitting spatially local sub-models using only neighbouring observations Jiang et al (2017). decomposed the area into geographic disjoint sub-areas, and fitted a local model in each sub-area Georganos et al (2019).…”
mentioning
confidence: 99%